2017
DOI: 10.1002/jcp.25811
|View full text |Cite
|
Sign up to set email alerts
|

LSP1, a responsive protein from Meyerozyma guilliermondii, elicits defence response and improves glycyrrhizic acid biosynthesis in Glycyrrhiza uralensis Fisch adventitious roots

Abstract: This research explored the effects of protein and polysaccharide in Meyerozyma guilliermondii on active compounds in Glycyrrhiza uralensis Fisch adventitious roots. In this study, a responsive protein LSP1 was purified from the Meyerozyma guilliermondii since the excellent induction. The contents of total flavonoids (3.46 mg · g ), glycyrrhizic acid (0.41 mg · g ), glycyrrhetinic acid (0.41 mg · g ), and polysaccharide (94.49 mg · g ) in adventitious root peaked at LSP1 group, which were 1.6, 3.4, 2.4, 2.0-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Studies have shown that Chryseobacterium in the rice phyllosphere has a role in suppressing rice blast disease [41], and Chryseobacterium isolated from potato tissue can act as a biocontrol agent against bacterial wilt disease [42]. Meyerozyma is a bene cial plant-microbe that promotes plant growth [43], triggers plant immune responses [44] and has multiple bene cial effects such as preventing post-harvest decay and insect pest control in fruits [45,46]. Vishniacozyma has a biocontrol effect against plant diseases caused by fungi [47,48] and can inhibit plant decay [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Chryseobacterium in the rice phyllosphere has a role in suppressing rice blast disease [41], and Chryseobacterium isolated from potato tissue can act as a biocontrol agent against bacterial wilt disease [42]. Meyerozyma is a bene cial plant-microbe that promotes plant growth [43], triggers plant immune responses [44] and has multiple bene cial effects such as preventing post-harvest decay and insect pest control in fruits [45,46]. Vishniacozyma has a biocontrol effect against plant diseases caused by fungi [47,48] and can inhibit plant decay [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Chryseobacterium in the rice phyllosphere has a role in suppressing rice blast disease [ 43 ], and Chryseobacterium isolated from potato tissue can act as a biocontrol agent against bacterial wilt disease [ 44 ]. Meyerozyma is a beneficial plant-microbe that promotes plant growth [ 45 ], triggers plant immune responses [ 46 ] and has multiple beneficial effects such as preventing post-harvest decay and insect pest control in fruits [ 47 , 48 ]. Vishniacozyma has a biocontrol effect against plant diseases caused by fungi [ 49 , 50 ] and can inhibit plant decay [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenoids, as a class of natural products with extensive biological activities, have attracted the attention of many researchers. Currently, the biosynthetic pathways of many triterpenoids have been successfully elucidated, such as ginsenosides [ 44 ], ganoderic acid [ 45 ] and glycyrrhizic acid [ 46 ]. However, acylated triterpenoids, especially benzoylated triterpenoids, are uncommonly seen and only present in plants belonging to the Helicteres genus.…”
Section: Discussionmentioning
confidence: 99%